2008
DOI: 10.1111/j.1742-7843.2008.00230.x
|View full text |Cite
|
Sign up to set email alerts
|

Atomoxetine Increases Histamine Release and Improves Learning Deficits in an Animal Model of Attention‐Deficit Hyperactivity Disorder: The Spontaneously Hypertensive Rat

Abstract: Substantial development in the pharmacological treatment for attention-deficit hyperactivity disorder (ADHD) has been made recently including approval of new non-stimulant agents targeting noradrenergic, histaminergic and dopaminergic systems. Among such, atomoxetine has been widely used, although its mechanism of action is poorly understood. It is known that central nervous system histamine is closely associated with cognition and it was recently shown that both atomoxetine and methylphenidate enhance cortica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 47 publications
(80 reference statements)
2
21
0
Order By: Relevance
“…Interestingly, neonatally 6-OHDA-lesioned rats have also been established as a model for attention deficit hyperactivity disorder (ADHD), with adulthood hyperactivity being attenuated by acute amphetamine or methylphenidate treatments (Shaywitz et al 1976;Kostrzewa et al 1994Kostrzewa et al , 2007Davids et al 2003). Histamine too (Liu et al 2008) and manganese (Bouchard et al 2007;Farias et al 2010) also have demonstrated roles in ADHD animal modeling.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, neonatally 6-OHDA-lesioned rats have also been established as a model for attention deficit hyperactivity disorder (ADHD), with adulthood hyperactivity being attenuated by acute amphetamine or methylphenidate treatments (Shaywitz et al 1976;Kostrzewa et al 1994Kostrzewa et al , 2007Davids et al 2003). Histamine too (Liu et al 2008) and manganese (Bouchard et al 2007;Farias et al 2010) also have demonstrated roles in ADHD animal modeling.…”
Section: Discussionmentioning
confidence: 98%
“…Rats trained in a five-choice serial reaction time task increased the percentage of correct responses and decreased the number of premature responses under the influence of reboxetine (89) or atomoxetine (90). In the spontaneously hypertensive rat, a genetic model for ADHD, atomoxetine ameliorated the learning deficits that typically exhibit these rats (91). Further, atomoxetine is an effective treatment for ADHD, especially in patients with comorbid disorders and those who do not tolerate well stimulant drugs (92).…”
Section: Iiipreclinical Indications – Behavioral Pharmacologymentioning
confidence: 99%
“…Atomoxetine and methylphenidate have also been shown to increase histamine release widely in the cortex (Fox, et al 2002). Through activation of histamine H3 receptor targets, atomoxetine improves spatial learning and memory deficits (Liu et al, 2008). Atomoxetine has been reported to exert beneficial effects on impairments of cognition due to a diversity of causes, including traumatic brain injury (Reid and Hamm, 2008), ADHD (Chamberlain et al, 2007) and schizophrenia (Rao et al, 2007; Friedman et al, 2004).…”
Section: Discussionmentioning
confidence: 99%